2005
DOI: 10.1590/s0103-97332005000600013
|View full text |Cite
|
Sign up to set email alerts
|

Computer modeling of a spinal reflex circuit

Abstract: We used a set of properties of the interactions among the spinal neurons in order to develop a computer model for a spinal reflex circuit. The model equations take into account the synaptic characteristics of the somatodendritic membrane of neurons in a morphofunctional unity of the spinal reflex activity. This model is based on the idea that the responses of spinal alpha-motoneurons to a sensorial stimulation can be modulated by the serial activation of a motor command chain. We developed a Fortran program fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Here, we adopted the same synaptic conditions used by Dalcin et al (2005). We have considered that the postsynaptic effect created by a single impulse reaching the presynaptic terminal was a subthreshold stimulus for the postsynaptic membrane.…”
Section: Description Of the Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we adopted the same synaptic conditions used by Dalcin et al (2005). We have considered that the postsynaptic effect created by a single impulse reaching the presynaptic terminal was a subthreshold stimulus for the postsynaptic membrane.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…where P R is the resting potential, P o is the synaptic reversal potential, τ P is the time constant of the period after the hyperpolarization potential, T R is the threshold potential at rest, T o is the excitation threshold after AP, τ H is the decay time constant for the relative refractory period and t p is the absolute refractory period (Dalcin et al 2005).…”
Section: Description Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In our model, these potentials are given by Equation 7: where P R is the resting potential, P o is the synaptic reversal potential, τ P is the time constant of the period after potential hyperpolarization, T R is the threshold potential at rest, T o is the excitation threshold after AP, τ H is the decay time constant for the relative refractory period, and t p is the absolute refractory period. Here, we adopted the same synaptic conditions as used by Dalcin et al (17).…”
Section: Model Adoptedmentioning
confidence: 99%
“…According to Abbot and Regeher (2004), the synaptic plasticity and the range of operation timescales suggest that long-term changes in the transmission properties of synapses provide a physiological substrate for learning and memory, whereas short-term changes support a variety of computations. Indeed, synapses have a very active role in information processing, and several computational models of learning and memory, as well as motor-sensory processing, have been proposed in the last years, based on present knowledge about synaptic characteristic and neuronal processing (Cruz et al, 2007;Becker, 2005;Cruz and Cortez, 2005;Dalcin et al, 2005). Neuroimaging experiments have revealed that emotionally charged stimuli have a greater modulatory effect on sensorial cortex and some subcortical structures than on the neutral ones (Mourão-Miranda, 2003, Lane 1999.…”
Section: Stress Effects On the Cerebral Functionsmentioning
confidence: 99%